The role of coalitions at international tariff negotiations: a CGE perspective - Florian Freund (Review of World Economics, 2021)
Developing countries coalitions form an integral part of tariff negotiations that take place under the aegis of the World Trade Organization. While there was only a single coalition in the 70s, their number increased to 31 in the year 2005. Despite the apparent proliferation of coalitions in tariff negotiations, little research on their theoretical and empirical implications has been produced. In particular, we lack an understanding of efficiency and equity effects of coalitions. By exploring this equity-efficiency nexus, the study finds that developing countries coalitions like the G-90 and the Least Developed Countries Group – while benefiting member countries – lead to less efficiency and less equity overall. Forming the Cairns Group, however, leads to a more efficient and equal distribution of the gains from trade.
Keywords: 330; Coalitions; Developing countries; Multilateral negotiations; CGE